The Perfect Apple is a Work of...Man - Dow Chemical Company (1945)
Color print advertisement for Dow Insecticides Division. The advertisement features a photograph of a bowl of red and green apples with a halved apple on a plate in the foreground. The accompanying text describes the use of insecticide sprays in commercial fruit growing operations. Notably, the advertisement was produced during World War II and bears the Company's wartime tagline "Dow: Chemicals Indispensable to Industry and Victory."
Keywords: Dow Chemical Company; Advertising; Chemical industry; Corporations; Insecticides; Fruit; Fruit--Diseases and pests; Insect pests--Control; Agricultural chemicals; Agricultural pests--Control; Advertising, Industrial